THE LOCATING RAINBOW CONNECTION NUMBERS OF LOLLIPOP AND BARBELL GRAPHS - Bustan, Ariestha Widyastuty; Talib, Taufan; Laamena, Novita Serly; Saputra, Lamanisa Rasid; Nurhayati, Nurhayati (PATTIMURA UNIVERSITY, 2025)
The concept of the locating rainbow connection number of a graph is an innovation in graph coloring theory that combines the concepts of rainbow vertex coloring and partition dimension on graphs. This concept aims to determine the smallest positive integer such that there exists a locating rainbow -coloring on the graph, ensuring that every vertex has a unique rainbow code. In this study, we investigate the locating rainbow connection number of the lollipop graph and barbell graph . Using a literature study method, hypotheses were formulated and proven through theoretical analysis. The results show that and .